Mentorship in Pharmacy Schools: Students’ Perspective - Jegede, Ayodapo Oluwadare; Erhun, Wilson Oyekigho; Oyinlola, Isaac Oluwadamilare (Indian Journal of Pharmaceutical Education and Research, 2023)
Introduction: Mentorship is seen as key to enhanced self-efficacy, and overall improvement in students' academic performance. However, information on how this affects academic performance in pharmacy schools in Nigeria is scarce. The study identified existing forms of mentorship, appraised the perceived contributions of mentorship to pharmacy students' academic performance, and assessed the benefits obtained by pharmacy students from student-mentor interactions in pharmacy schools in Southwest Nigeria. Materials and Methods: The study was a cross-sectional survey of pharmacy students (330) in four accredited pharmacy schools Obafemi Awolowo University (OAU), University of Ibadan (UI), Olabisi Onabanjo University (OOU), and University of Lagos (UNILAG) in Southwest Nigeria. Data collection involved the use of a pre-tested and validated questionnaire. The data collected was analyzed using appropriate descriptive and inferential statistics at p < 0.05. Results: The results showed that peer mentorship (informal mentorship) (29%) was prevalent even though there was existing formal mentorship in the faculties. The students indicated that lecturers served as professional models (Weighted Average (WA) = 3.91), contributed to the advancement to the next class (WA= 4.15), and impacted their academic performance (WA= 4.16). Mentorship impacted the study habits of UI students the most (Mean Rank= 196.90), attitude to work for OAU students (Mean Rank= 199.86), and students aged 26 and above were more positively inclined to their lecturers serving more as professional role models than those who were younger. Conclusion: The study concluded that informal peer mentorship is predominant in pharmacy schools even with the existing formal staff advisory system. Mentorship is significant in role modeling and promoting academic achievement. Mentorship also impacts improved self-confidence, improved study habits, and improved attitude to academic work, resulting in better academic performance.
Keywords: Mentorship; Learning; Academic performance; Education; Study habits; Mentees